1998
DOI: 10.1002/(sici)1097-4547(19980701)53:1<86::aid-jnr9>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent loss of corticosterone modulation of central serotonin 5-HT1A receptor binding sites

Abstract: A loss of endocrine and neurotransmitter system interactions, including corticosterone regulation of 5-HT1A receptors, may underlie the age-related deficits in the hypothalamic-pituitary-adrenal (HPA) axis including adapting to stress. In this study, female Fischer 344 rats, (ages 3, 13, and 18 months), were bilaterally adrenalectomized and supplemented for 3 weeks with placebo or corticosterone (200 mg or 600 mg) containing 21 day sustained-release pellets implanted subcutaneously (LC, MC, or HC, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…In contrast, the 5-HT 2A receptor in the hippocampus failed to respond to these hormonal conditions at any age. The baseline density of cortical 5-HT 1A receptors showed a limited dependence on plasma corticosterone concentrations, in agreement with previous data from our laboratory obtained via equilibrium binding analysis (Maines et al, 1998). Thus, the hippocampus appears to be a region of interest in which This decrease in 5-HTT sites resulted in levels of binding that were significantly lower than that in 13-and 18-month HC groups as well, showing an age-dependent effect.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, the 5-HT 2A receptor in the hippocampus failed to respond to these hormonal conditions at any age. The baseline density of cortical 5-HT 1A receptors showed a limited dependence on plasma corticosterone concentrations, in agreement with previous data from our laboratory obtained via equilibrium binding analysis (Maines et al, 1998). Thus, the hippocampus appears to be a region of interest in which This decrease in 5-HTT sites resulted in levels of binding that were significantly lower than that in 13-and 18-month HC groups as well, showing an age-dependent effect.…”
Section: Discussionsupporting
confidence: 90%
“…In animal models that manipulate corticosterone concentrations, the 5-HT 1A receptor down-regulates in density in young animals when exposed to high levels of circulating corticosterone (Mendelson and McEwen, 1992). Equilibrium binding studies have also demonstrated that 5-HT 1A receptor density is differentially regulated by varied corticosterone across aging, with decreased hippocampal regulation in older age groups (Maines et al, 1998), and, thus, represent changes in the regulation of the serotonergic system by glucocorticoids with aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Makisumi et al (1998) suggest that glucocorticoids are permissive for the hyperthermic response and MA (10 mg/kg 3 4) induces a marked increase in corticosterone that lasts for at least 3 days . Interestingly, we also noted slightly higher 5-HT levels in the ADX groups, an observation that may benefit from further investigation since it is known that the serotonergic system and corticosterone are linked (Fuller, 1992;Maines et al, 1998;Meijer et al, 1997). Taken together, the data suggest that hyperthermia and/or increased corticosterone levels may have a larger role in MA-induced serotonergic reductions than in dopaminergic reductions.…”
Section: Discussionsupporting
confidence: 58%
“…This may be an explanation for the more frequent accidental hypothermia in the elderly and the difficulties of the older experimental animals in the present study, since shivering thermogenesis is more energy consuming than the non-shivering thermogenesis observed in younger rats. Furthermore, it is known that elderly subjects possess a diminished capacity of the hypothalamic-pituitary-adrenal axis and a reduced corticosterone output and thus have major problems coping with stress (Maines et al, 1998;Workel et al, 2001). This may explain the difficulties of the older rats in our study to maintain body temperature in the course of the combined surgical intervention.…”
Section: Discussionmentioning
confidence: 91%